The Prevalence of Abnormal Cervical Pap Smears in Women with Morbid Obesity in Dubai, United Arab Emirates - AbdullGaffar, Badr; Hotait, Hassan; Essa, Azza; Tahlak, Muna (Journal of Women's Reproductive Health, 2016)
Background and Objectives: The prevalence of abnormal cervical cytology in morbidly obese women using ThinPrep® liquid-based Pap Test™ and HPV DNA Test™ is unknown. We aimed to investigate whether women with morbid obesity have a higher frequency of abnormal Pap smears compared with nonobese women, and to explore the rate of Pap smear screening in morbidly obese women. Design and Setting: We conducted a retrospective study over five years in two general government hospitals in Dubai. Patients and Methods: We screened ThinPrep slides and HPV DNA of morbidly obese women and nonobese women. The age, ethnicity, demographic and socioeconomic backgrounds of the two groups were matched. We studied hypertension (HTN), diabetes (DM), infertility, sexually transmitted diseases (STD), connective tissue disease (CTD), immunosuppression and oral contraceptive pills (OCP) as potential risk cofactors. Results: Only 90 (29%) out of 310 morbidly obese women had had Pap tests. They showed more prevalence (P<0.05) of ASC-US, high-risk HPV DNA and LSIL 16 positive (18%) (95% CI: 7.0, and of endometrial AGCs {4 positive (4.5%) (95% CI: 0.3-13.5)} than the nonobese women (n=8175), {279 positive (3%) (95% CI: 3.0-3.8} , and {2 positive (0.024%) (CI:0.01-0.09)}. There were no endocervical AGCs, HSIL or squamous cancer in morbidly obese women. DM, HTN, OCPs, CTD and STD were more common in morbidly obese women having abnormal Pap smears. Conclusions: Low-grade squamous abnormalities, high-risk HPV, and endometrial AGCs are more frequent in morbidly obese women than in nonobese women. Women with morbid obesity have a low rate of cervical screening. This, among other factors, could increase the risk of these women to abnormal cervical cytology. This vulnerable group should benefit from more frequent cervical cytology screening. Appropriate clinical and educational measures should be implemented to encourage compliance to Pap smears. Weight reduction might help.
Keywords: abnormal Pap smears; HPV; morbid obesity; ThinPrep; women.